การพัฒนารูปแบบการเรียนรู้โปรแกรมหุ่นยนต์ด้วยวัฏจักรการเรียนรู้ 7E เพื่อส่งเสริมความสามารถในการแก้ปัญหาอย่างสร้างสรรค์ - ศรีวงษ์ญาติดี, ศศิธร; สงคราม, เนาวนิตย์ (An Online Journal of Education, 2018)
The purpose of this research was to develop robotics learning model using the 7E learning cycle to enhance creative problem solving ability. The subjects of the survey consisted of 6 experts in robotics experts, instructional design experts and creative problem solving experts. The research instruments use in this study consisted of an expert’s interview from and the model evaluation form. The developed model consisted of seven phases as follows: 1) Engagement phase; 2) Exploration phase; 3) Explanation phase; 4) Elaboration phase; 5) Exchange phase; 6) Evaluation phase; and 7) Extension phase. The importance of robotics learning model using the 7E learning cycle to enhance creative problem solving abilities consisted of 4 components: 1) understanding the challenge; 2) generating ideas; 3) deciding for action; and 4) supporting solutions. Evaluation results showed that the model is very appropriate and the experts have commented for the use of the model to be interesting, but consider the time of use and had opinions for the model in real situations to specify more clearly the evaluation of students.